5y-1+2y=3

Simple and best practice solution for 5y-1+2y=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y-1+2y=3 equation:


Simplifying
5y + -1 + 2y = 3

Reorder the terms:
-1 + 5y + 2y = 3

Combine like terms: 5y + 2y = 7y
-1 + 7y = 3

Solving
-1 + 7y = 3

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 7y = 3 + 1

Combine like terms: -1 + 1 = 0
0 + 7y = 3 + 1
7y = 3 + 1

Combine like terms: 3 + 1 = 4
7y = 4

Divide each side by '7'.
y = 0.5714285714

Simplifying
y = 0.5714285714

See similar equations:

| -46-12x=-9x+41 | | Y=17-0.5(10.5) | | -4+3x=6x-2 | | 17-2p=4p-5 | | x=-6-2y | | 26=4x+4y | | -3x-62=113+4x | | 80+42+2x=180 | | 25x+1=6252x+3 | | y=x^2-8x+25 | | 15k=(9-k)k | | 2x-1/3-x+13/24=3x+5(5x+5)/8 | | -60+11x=-5x+132 | | 3x-2(17-0.5x)=8 | | n^2+16n+52=4 | | 50=-7x+3x+2 | | 0=-20.76x+30.12 | | 5b^2=28-31b | | X^2=1.34 | | 700-600=00.3x | | 11x-67=31+4x | | y=-20.76x+30.12 | | 3x+3=3(1+x) | | 2q+66=q+72 | | -3x+32-7x=-2(5x+1) | | 8v^2+40v-112=0 | | 4z+3-9z= | | 100g+15=8 | | x*88(5+0.77)-2.4=57.6 | | -3+32-7x=-2(5x+1) | | 2x=4-9x | | 5x-7+10x+9= |

Equations solver categories